2004
DOI: 10.1039/b402477j
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Sonogashira coupling reactions in an ionic liquid, effected in the absence of both a copper salt and a phosphineElectronic supplementary information (ESI) available: experimental details. See http://www.rsc.org/suppdata/cc/b4/b402477j/

Abstract: 3 0 6C h e m . C o m m u n . , 2 0 0 4 , 1 3 0 6 -1 3 0 7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…By comparison of the efficiency of conversion of iodobenzene and its electron-donating 4-methoxy ( 1d ) and electron-withdrawing 4-nitro ( 1m ) derivatives with different aliphatic acetylenes ( 4 , 6 , and 8 ), no significant differences in isolated yields were observed (Table 4, Table 5 and Table 6) verifying the wide range of functional group tolerance by side of acetylenic substrates, as well. Same results were reported by Alper and co-workers, who perform this reaction in [BMIM][PF 6 ] as alternative solvent [22].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…By comparison of the efficiency of conversion of iodobenzene and its electron-donating 4-methoxy ( 1d ) and electron-withdrawing 4-nitro ( 1m ) derivatives with different aliphatic acetylenes ( 4 , 6 , and 8 ), no significant differences in isolated yields were observed (Table 4, Table 5 and Table 6) verifying the wide range of functional group tolerance by side of acetylenic substrates, as well. Same results were reported by Alper and co-workers, who perform this reaction in [BMIM][PF 6 ] as alternative solvent [22].…”
Section: Resultssupporting
confidence: 81%
“…The series of these alternative media can implicitly be continued by ionic liquids (ILs) [20], which have attracted considerable attention, due to their extremely low vapor pressure, good solvating properties, reasonable thermal stability, and easily tuneable physical properties [21]. Accordingly, the Sonogashira reactions were also successfully performed in conventional ionic liquids such as [BMIM][PF 6 ] [2225], [BMIM][BF 4 ] [23], [HMIM][BF 4 ] [24], [EMIM][NTf 2 ] [26], [nBuPy][X] (X = PF 6 – , BF 4 – , NO 3 – ) [27], [DectBu 3 P][BF 4 ] [28]. It was found that some of these systems could operate copper-free [25,27,29] and/or auxiliary base-free conditions [30].…”
Section: Introductionmentioning
confidence: 99%
“…1‐Nitro‐4‐(phenylethynyl)benzene ( 3 j ) [CAS: 1942‐30‐9]: According to the general procedure by using 1‐iodo‐4‐nitrobenzene (125 mg, 0.5 mmol), ethynylbenzene (51 mg, 0.6 mmol), Pd/ICCP (9 mg, 0.005 mmol), and potassium carbonate (138 mg, 1.0 mmol) in EtOH (6 mL) for 4 h to afford 3 j (101.6 mg, 0.44 mmol, 91 %) as a white solid. 1 H NMR (400 MHz, CDCl 3 ): δ =8.21 (d, J= 8.7 Hz, 2 H), 7.66 (d, J= 8.8 Hz, 2 H), 7.56 (dd, J= 5.9, 2.6 Hz, 2 H), 7.46–7.32 ppm (m, 3 H); 13 C NMR (101 MHz, CDCl 3 ): δ =147.11, 132.37, 131.96, 130.37, 129.40, 128.66, 123.74, 122.23, 94.83, 87.68 ppm; GC–MS: m / z : 222.9.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a problem that accompanies soluble Pd complexes is the loss of the expensive metals. [10,11] Consequently, most of the traditional methods were economically and environmentally problematic, and modifications were carried out by introducing systems such as those that were phosphine-free, [12][13][14] copper-and amine-free, [15,16] copper-catalyzed Pd-free, [17][18][19] and the use of other transition metals such as Fe, [20] Co, [21] Ni, [22][23][24][25][26][27][28] Ru, [29] and In, [30] as well as the use of a solid supported catalyst. [15,[31][32][33] Nickel is a promising and cheaper alternative to the use of palladium as a transition-metal catalyst in coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The electron-neutral, electron-rich, and electron-poor aryl iodide and bromides were treated with phenyl acetylene and the coupled products were obtained in reasonable yields. The reaction of aryl chlorides was performed in the presence of TBAB (0.1 mmol) as an additive (Table 5, entries [10][11][12]. Comparison of the presented catalytic system with other Ni- [a] Reaction conditions: iodobenzene (1 mmol), phenylacetylene (1.2 mmol), base (2 mmol) Ni catalyst (10-5 mmol %), CuI (0.1-0.05 mmol %) and 3 mL of solvent at 120 8C.…”
mentioning
confidence: 99%